IN VITRO STUDY ON THE ANTIPLASMODIAL POTENTIAL OF METHANOLIC EXTRACT OF LEAVES OF SALVADORA PERSICA L (Journal of Medical & Health Sciences Review, 2025)
Malaria is one of the major global health problem that is caused by Plasmodium parasites and spread by Anopheles mosquitoes. According to an estimate by WHO in 2019, about 227 million cases of malaria with a total death toll of 558,000 has been recorded. The number increased to 241 million with 667,000 deaths in 2020. The main cause of the malaria is P. falciparum (60%) followed by P. vivax with a percentage of 40. But the report cases for P. vivax is increasing each year. In Pakistan, about 64% of malarial cases is due to plasmodium vivax. Assessments of transmission and occurrence at such passion is a grave problem. The key challenges to control P. vivax malaria is because of the dearth of treatment options to clear hypnozoites, the resistancy of malarial parasites to several existing antimalarial medications, the expenses associated in managing malaria in low income countries and its associated side effects is a major problem in combating malaria.  Due to these challenges, there is an inadequate advancement in the production of experimental study tools, thus hindering production of new drugs and vaccines. New drugs are required to avert the Plasmodium strains. Therefore, in this study we investigated the antiplasmodial activity of Salvadora persica, also known as Miswak. The leaves methanolic extract of S. persica was formulated and different concentrations were used against the malarial parasite Plasmodium vivax. S. persica. Our results revealed that methanolic extract of S. persica leaves possess antiplasmodial activity and the inhibition has been found to be dose dependent and has displayed maximum growth inhibition of about 66.53%. Our results indicated that S. persica can be used as strong antimalarial agent.